2002
DOI: 10.1123/jab.18.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Selected Lower Limb Joint Kinetic Parameters during Vertical Jump

Abstract: Stability and consistency is a critical aspect in joint kinetic measurements. By applying a statistical technique, called sequential estimation procedure, the aim of this work was to determine the minimum number of trials required to obtain a stable mean for peak hip, knee, and ankle moments and powers during vertical jump. Nine competitive track and field sprinters (21.7 ± 3.5 yrs, 177.6 ± 4.3 cm, 70.8 ± 3.6 kg) performed 5 series of 5 double-legged maximum-height countermovement vertical jumps. From force pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
1
18
0
3
Order By: Relevance
“…The general tendency can be found, that measured parameters show a higher reproducibility than calculated complex parameters, which might be caused on data acquisition and calculation methods. Rodano and Squadrone (2002) found CVs for moments and power in the leg joints during vertical jumps similar to those for the parameters of energy production presented in this study.…”
Section: Article In Presssupporting
confidence: 79%
See 1 more Smart Citation
“…The general tendency can be found, that measured parameters show a higher reproducibility than calculated complex parameters, which might be caused on data acquisition and calculation methods. Rodano and Squadrone (2002) found CVs for moments and power in the leg joints during vertical jumps similar to those for the parameters of energy production presented in this study.…”
Section: Article In Presssupporting
confidence: 79%
“…For clinical research situations and different forms of locomotion several reliability and variability studies have been carried out (e.g. DeVita and Bates, 1988;Bates et al, 1983;Hamill and McNiven, 1990;Heiderscheit et al, 1999;Diss, 2001;Rainoldi et al, 2001;Rodano and Squadrone, 2002;Karamanidis et al, 2003Karamanidis et al, , 2004. In applied sport research reproducibility, reliability and variability studies, respectively, are quite rare (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous other studies have strongly suggested that multiple trial protocols are necessary for obtaining stable results in the assessment of lower limb function in a variety of activities. [29][30][31] For example, Rodano and Squadrone 30 reported that a 12 trial protocol was needed for establishing stable results for power outputs of the ankle, knee and hip joints during vertical jumping. James et al 31 indicated that a minimum of four and possibly as many as eight trials should be performed to achieve performance stability of selected ground reaction force variables during landing experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential analysis technique has been used to determine trials to stability in a number of biomechanical measures including ground reaction forces during running (Bates, Osternig, Sawhill, & James, 1983), walking (Hamill & Mcniven, 1990), landing (James, Herman, Dufek, & Bates, 2007), jumping (Racic, Pavic, & Brownjohn, 2009), cricket bowling (Stuelcken & Sinclair, 2009), joint power and moment during vertical jumping (Rodano & Squadrone, 2002) and time to postural stability (Colby, Hintermeister, Torry, & Steadman, 1999). Most research has concentrated on discrete kinetic variables from lower limb movements, while kinematic variable stability has only been addressed in one study (Amiri-Khorasani, Osman, & Yusof, 2010).…”
Section: Introductionmentioning
confidence: 99%